The relationship between workplace psychosocial environment and retirement intentions and actual retirement: a systematic review - Browne, Peter (Eur J Ageing, 2018)
Psychosocial work characteristics are potential determinants of retirement intentions and actual retirement. A systematic review was conducted of the influence of psychosocial work characteristics on retirement intentions and actual retirement among the general population. This did not include people who were known to be ill or receiving disability pension. Relevant papers were identified by a search of PubMed, PsycINFO and Web of Science databases to December 2016. We included longitudinal and cross-sectional papers that assessed psychosocial work characteristics in relation to retirement intentions or actual retirement. Papers were filtered by title and abstract before data extraction was performed on full texts using a predetermined extraction sheet. Forty-six papers contained relevant evidence. High job satisfaction and high job control were associated with later retirement intentions and actual retirement. No consistent evidence was found for an association of job demands with retirement intentions or actual retirement. We conclude that to extend working lives policies should increase the job control available to older employees. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10433-018-0473-4) contains supplementary material, which is available to authorized users.